The role of postoperative radiotherapy in patients with uterine sarcomas: A PSM-IPTW analysis based on SEER database - Hao, Zhimin; Yang, Sufen (Frontiers in Surgery, 2022)
Abstract Objective The optimal adjuvant therapy for uterine sarcomas remains poorly determined due to its rarity and histological diversity. The purpose of the study is to explore and characterize the association between utilization of radiotherapy and survival outcome in patients with surgically resected uterine sarcomas. Methods We collected data regarding uterine sarcomas which were confirmed after total hysterectomy between 2010 and 2018 period from the latest version of the Surveillance, Epidemiology, and End Results (SEER) database. Initially, 1-, 3- and 5-year survival rate were calculated to predict potential risk factors and possible role of adjuvant chemotherapy and radiotherapy. Propensity score matching (PSM) and inverse probability treatment weighting (IPTW) technique were employed to balance confounding factors in the utilization of additional therapy. Multivariate and exploratory subgroup analyses were respectively conducted to evaluate the impact of adjuvant therapy on overall survival (OS) and cause-specific survival (CSS). Results A total of 2897 patients were enrolled in the analysis. Survival benefit at 1-, 3-and 5-year after initial treatment was observed in the group of radiotherapy given, however, poorer prognosis in the group of chemotherapy administration. Accordingly, chemotherapy was enrolled as a confounding factor when stratifying and matching patients by receipt of radiotherapy. Prior to and after PSM-IPTW adjustment, radiotherapy both demonstrated beneficial effect on OS and CSS based on multivariate analysis. Further subgroup analysis indicated radiotherapy improved OS and CSS among a subset of patients in stage II-IV, particularly with uterine leiomyosarcoma, tumor grade IV, bigger tumor size than 100mm and even with chemotherapy administration. Conclusions Adjuvant radiotherapy in uterine sarcomas after hysterectomy might be underutilized, and proper use of adjuvant radiotherapy combined with chemotherapy after surgery in advanced-stage and high-risk patients might improve survival.